Theoretical-experimental Determination of Nonlinear Crack Parameters in the Cracked Beam under Nonlinear Low Amplitude Vibration - M. Rezaee (Ravish/hā-yi ̒adadī dar Muhandisī, 2017)
In the vibration of a cracked structure with small amplitude oscillations, the crack necessarily is not fully open or fully closed. Therefore, in order to provide a realistic model for the crack, one should relate the stiffness and damping at the crack location to the amount of the opening of the crack. In this study, a continuous model for vibration of a beam with a fatigue crack under low amplitude oscillations is presented in which the crack is not fully open or fully closed. By introducing a nonlinear model for the crack, the equation governing the vibration of the cracked beam is extracted. In order to consider the nonlinear behavior of the crack and to take into account the energy loss at the crack during the vibration, the bending moment at the crack location was considered as a nonlinear function of the angle of crack opening and its variations with respect to the time. The governing nonlinear equation is solved using the perturbation method. The solution reveals the dependency of the resonance frequency on the vibration amplitude. Analytical and explicit expressions are also derived for the nonlinear stiffness coefficient and the damping coefficient of the crack at the crack location. Finally, using the derived expressions for the crack parameters and experimental tests results for cracked beam, the nonlinear stiffness coefficient and the damping coefficient at the crack location is obtained.